2016
DOI: 10.5194/amt-9-1545-2016
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of 15 aerodynamic particle size spectrometers (APS 3321): uncertainties in particle sizing and number size distribution

Abstract: Abstract. Aerodynamic particle size spectrometers are a well-established method to measure number size distributions of coarse mode particles in the atmosphere. Quality assurance is essential for atmospheric observational aerosol networks to obtain comparable results with known uncertainties. In a laboratory study within the framework of ACTRIS (Aerosols, Clouds, and Trace gases Research Infrastructure Network), 15 aerodynamic particle size spectrometers (APS model 3321, TSI Inc., St. Paul, MN, USA) were compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 7 publications
(15 reference statements)
3
35
0
Order By: Relevance
“…Furthermore, the accuracy of the counting of particles was generally similar with small differences in the lower size range, where the APS seemed to be less accurate, and underestimating particles <0.7 µm. Pfeifer et al (2016) found for the APS that the variability in counting efficiency for particles <0.9 µm is 60% between different tested machines, which underline the findings of Peters et al (2006) . The OPC was less accurate in counting particles >2.5 µm, however, for this study this size range is not investigated .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the accuracy of the counting of particles was generally similar with small differences in the lower size range, where the APS seemed to be less accurate, and underestimating particles <0.7 µm. Pfeifer et al (2016) found for the APS that the variability in counting efficiency for particles <0.9 µm is 60% between different tested machines, which underline the findings of Peters et al (2006) . The OPC was less accurate in counting particles >2.5 µm, however, for this study this size range is not investigated .…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, we developed two fit curves to convert Dylos for particles <0.9 µm is 60% between different tested machines, which underline the findings of Peters et al (2006). 25 The OPC was less accurate in counting particles >2.5 µm, however, for this study this size range is not investigated. 29 In two additional studies, it was shown that both the APS and the OPC mass concentrations were well in line with gravimetric samples, indicating that these devices are fairly capable of measuring PMC, 30,31 and are usable as a device to evaluate the performance of other real-time instruments.…”
Section: Discussionmentioning
confidence: 90%
“…The PNSD uncertainty determined 30 with the MPSS is approximately 10 %. The uncertainty of an APSS is between 10-30 %, depending on the size range (Pfeifer et al, 2016). The uncertainty of the MAAP is also within 10 % as determined by Müller et al (2011).…”
Section: Research Observatory Melpitzsupporting
confidence: 58%
“…For the multiple charge correction (Wiedensohler, 1988) of the MPSS data, the APS data was accounted for in the inversion of the measured PNSD (Pfeifer et al, 2016). The combined PNSD is then given on the base of the volume equivalent particle diameter.…”
Section: Particle Number Size Distributionmentioning
confidence: 99%